Baremación preliminar de un cuestionario para la modificación del consumo de alcohol, elaborado con fundamento en el modelo transteórico. - Flórez Alarcón, Luis (Acta Colombiana de Psicología, 2001)
The Stages Questionnaire for Alcohol Comsumption (CEMA) was designed and applied to 500 Bogota university students for the evaluation of alcohol abuse, consumption temptation, self-efficacy, significance awarded to consumption and readiness to change, as well as some other criteria which allow subjects to be classified under any of the stages of the Transtheoretical Model (TTM). The purpose was to analyze the reliability and validity of the questionnaire, and to obtain its standards. We found that the various scales included in the questionnaire show good Crombach reliability indexes. We also isolated the evaluating subfactors, after the main component analysis system, with Varimax rotation and Kaiser normalization, which determines their applicability, whether total or partial. For getting the scale standards, we used percentages, thus facilitating their comparison, since the number of items included is different in each case. We are submitting the- standards related to each scale, on a global basis, as well as discriminated standards with regard to the gender. It is also suggested that a category system be used to allow in the future a qualitative interpretation of a subject’s score, in any of the scales.